Life cycle and pathogenicity of native isolate Heterorhabditis sp. SL0708 (Rhabditida: Heterorhabditidae) - SÁENZ-A., ADRIANA; LÓPEZ-N., JUAN CARLOS (Revista Colombiana de Entomología, 2011)
Entomopathogenic nematodes of the genus Heterorhabditis are important agents for the biological control of pests. We determined the pathogenicity, symptomatology, in vivo multiplication and life cycle in larvae of Galleria mellonella (Lepidoptera: Pyralidae) for a nematode isolated from Alcalá, Valle del Cauca, Colombia called Heterorhabditis sp. SL0708. A sample of 1000 cm3 of soil collected from grass, coffee, plantain and guadua was processed. To establish virulence, a one-to-one bioassay was conducted. At 120 hours after infection, 20larvae were kept in incubation to record the accumulated production of infective juveniles (IJ). The general life cycle and the percentage of penetration were determined by dissecting 100 larvae every 8, 12 and thereafter 24 hours for 19 days. The soil samples from bamboo presented a mortality of IJ of 84% IJ between 24 and 72 hours after exposure. The symptomatology exhibited by the larvae was typical of species from the genus Heterorhabditis. Percent penetration was 35% (10-80%), which corresponds to the entrance of one to eight IJ in 24 hours. The life cycle of Heterorhabditis sp. SL0708 consists of a long cycle of two generations and a short cycle of one generation. This native nematode has eight developmental stages: egg, four juvenile stages (J1 J2, IJ-J3, J4) separated by moltings, and adult hermaphrodites, males and females. The cycle had a duration of19 days from infection to IJ recovery and each larva produced an average of 200,000 IJ.